TECHNICAL GUIDANCE AND LEADERSHIP COMPETENCE OF MERAH PUTIH COOPERATIVE CHAIRPERSONS - Imam Sholihin; Riswan (International Journal of Multidisciplinary Reseach, 2026)
The establishment of Merah Putih Village/Sub-district Cooperatives requires chairpersons who can make sound decisions, communicate effectively, and foster collaboration among members. This study examines the effects of material quality, instructor competence, learning methods, and post-training mentoring on the leadership competence of Merah Putih Cooperative chairpersons in South Lampung Regency. A quantitative explanatory design was employed using a census of all 95 eligible cooperative chairpersons. Data were collected through a validated and reliable five-point Likert-scale questionnaire and analyzed using multiple linear regression after testing normality, multicollinearity, and heteroscedasticity assumptions. All four independent variables had positive and statistically significant partial effects on leadership competence. The overall model was significant (F = 16.057, p < 0.001) and explained 41.6% of the variance in leadership competence (R² = 0.416). Material quality was the strongest predictor (β = 0.395), followed by learning methods (β = 0.365), post-training mentoring (β = 0.285), and instructor competence (β = 0.272). The findings indicate that relevant content, experiential learning, competent instructors, and structured follow-up support should be integrated into technical guidance programs for cooperative leaders.